CULTURAL PROMOTION THROUGH NUSANTARA TRADITIONAL COSTUME FASHION SHOW AT UTHM MALAYSIA - Wesmi Huriyaty; Sulastri Sulastri; Milawati Milawati; Muhammad Thamrin; Suryani Suryani; Putri Wahyuni; Maryadin Maryadin; Yatasya Ananda Shophia; Rimayang Anggun Laras Prastianty Ramli; Rona Tanjung; Mira Yona; Magneta Hisyam; Denny Ammari Ramadhan; Hanafi Siregar; Habibuddin Nasution; Umi Kartini Binti Rashid; Mohd Asmadi Bin Mohd Angsor; Nur Aina Binti Azizan; Nur Athirah Binti Mohd Borkhan; Mohd Khairul Naser Bin Ibrahim (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This community service article describes a cultural promotion activity through a Nusantara traditional costume fashion show under the theme “Wonderful Indonesia” at Universiti Tun Hussein Onn Malaysia. The activity responded to the need for more direct, visual, and participatory cultural communication between Indonesian and Malaysian academic communities. It was implemented on 16 April 2026 at the Audio Visual Studio of Tunku Tun Aminah Library, involving Universitas Riau Kepulauan students as performers and organizers, with support from traditional costume studios and salons in Batam. The method used a participatory service design consisting of preparation, partner coordination, costume selection, runway performance, cultural narration, final parade, documentation, and qualitative reflection. The activity presented traditional attire from Minangkabau, Betawi, South Sulawesi, Sunda, Solo, Papua, and Aceh. The results indicate that fashion show performance can function as an accessible cultural diplomacy medium because it combines visual aesthetics, identity narration, and audience engagement. The activity strengthened Indonesian cultural visibility in an international academic setting and produced recommendations for broader audience involvement, stronger digital promotion, and follow-up cultural workshops.